2015
DOI: 10.3238/arztebl.2015.0535
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Following Cholecystectomy and Herniotomy

Abstract: These findings suggest that there is potential for improvement in preoperative risk identification, complication avoidance, and the early recognition and treatment of complications, as well as in safe surgical technique. Measures to lower the mortality associated with herniotomy and cholecystectomy would lessen patients' individual risk and thereby improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Esto puede obedecer al hecho de que esta población tiende a presentar otras comorbilidades al momento de la cirugía, como se evidencia en un estudio realizado en población colombiana, en el que los mayores de 65 años tenían con mayor frecuencia condiciones como hipertensión arterial, diabetes mellitus y clasificación ASA III-IV al momento de ser llevados a colecistectomía 8 . Nimptsch et al, en 2015 encontraron que el riesgo de morir luego de una colecistectomía es 10 veces mayor en pacientes mayores de 65 años que en personas jóvenes 9 .…”
Section: Discussionunclassified
“…Esto puede obedecer al hecho de que esta población tiende a presentar otras comorbilidades al momento de la cirugía, como se evidencia en un estudio realizado en población colombiana, en el que los mayores de 65 años tenían con mayor frecuencia condiciones como hipertensión arterial, diabetes mellitus y clasificación ASA III-IV al momento de ser llevados a colecistectomía 8 . Nimptsch et al, en 2015 encontraron que el riesgo de morir luego de una colecistectomía es 10 veces mayor en pacientes mayores de 65 años que en personas jóvenes 9 .…”
Section: Discussionunclassified
“…In our series, the crude mortality rate was 1.1%, significantly higher among patients who presented with HF (12.9%) than among those who did not (1%) ( p < 0.001). Previous studies have also demonstrated a strong association in patients with heart failure or dilated cardiomyopathy, whose risk of death is 3.6 times higher than that of patients for whom no such comorbidity is coded [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The operation for which the patients were scheduled was just a minor surgical procedure [13]. Still, their fear should not be underestimated, especially in view of the fact that deaths after cholecystectomy or hernia repair do occur, although they are rare [16]. It is understandable then that some of our subjects declared to be in mortal fear.…”
Section: Discussionmentioning
confidence: 99%